RUPTURE OF THE UTERUS ACCORDING TO THE SCAR AFTER MYOMECTOMY, CESAREAN SECTION. DESCRIPTION OF CLINICAL CASES - Сергей Владимирович Баринов; Юлия Игоревна Тирская; Алина Валерьевна Фоломеева; Ольга Альбертовна Гребенюк; Татьяна Владимировна Пак; Татьяна Владимировна Кадцына; Оксана Вячеславовна Лазарева; Юрий Игоревич Чуловский (The Publishing House Medicine and Enlightenment, 2024)
Rupture of the uterus along the scar after a cesarean section, myomectomy or other interventions on the uterus can occur both during pregnancy and childbirth. This complication leads to intra-abdominal bleeding, often results in hysterectomy and is associated with a risk of maternal and perinatal mortality. Previous vaginal birth with a uterine scar is considered to be a predictor of successful delivery. This article describes cases of uterine rupture in patients with a scar who had previously delivered vaginally after surgical interventions in the uterus. These pregnant women had no signs of scar failure according to ultrasound examination, which indicates that childbirth with a uterine scar always requires increased attention to the patient's complaints, a careful assessment of clinical symptoms during their management and special monitoring of the condition of the mother and fetus.